Transdermal Fentanyl Patch as a Component of Multimodal Analgesic Regimen for Acute Postoperative Pain - Lakshmi, S. Kalyani Surya Dhana; Chandrasekhar, C. N. (New Horizons in Medicine and Medical Research Vol. 2, 2022)
Background: Acute pain in the postoperative period has an incidence of around 80%, and nearly 86% have moderate to severe pain [1]. Enhanced recovery after surgery (ERAS) recommends the multimodal analgesic regimen to reduce the postoperative pain and improve the outcomes [2]. The multimodal analgesic regimen prioritises the reduction on dependence on opioid analgesia, and pain is addressed at different levels utilising different mechanisms of action, thereby alleviating pain and decreasing complications associated with any individual drug. Various methods (regional anaesthesia, nerve blocks, local infiltration) and medications including non opiate like Nonsteroidal anti-inflammatory drugs, paracetamol, Cyclooxygenase2 inhibitors, NMDA receptor antagonists, gabapentins, pregabalins, and alpha 2 receptor agonists and lastly opioids are incorporated into the treatment regimen as per requirement. Transdermal fentanyl patch provides steady state plasma levels after 12-24 hrs of application, thereafter the plasma levels are constant for the remaining 72 hours providing effective analgesia [3]. The primary objective of this study was to assess pain relief in the postoperative period with transdermal fentanyl patch in the opioid naïve patient and secondary objective was to assess any associated side effects. Material and Methods: A total of 44 patients were divided into two groups. Groups were named as FP (Fentanyl patch) and P ( Placebo). The Patch was placed 10-12 hours before surgery and patient was monitored for 72 hours postoperatively for pain by NRS (Numeric Rating Scale). All of the patients were given Paracetamol and Diclofenac Sodium on a regular basis. If the NRS scale was greater than 5, tramadol was administered as a rescue analgesic. Data was analysed using Indostat services' Windows stat version 9.2. Results: Over 72 hours, there was a statistically significant difference in Tramadol intake between patients in the FP group (19.44mg) and the P group (72.22mg). The Numerical Rating scale was also much lower in the FP group at 8,16,24,32,40,48,56,64 and 72 hours. Maximum difference in the pain score was observed at 24 hours for the FP group. There was no difference in the incidence of sedation, pruritus, respiratory depression, nausea and vomiting scores in the two groups. Conclusion: Transdermal Fentanyl Patch of 25µg/hr when applied 10-12 hours before surgery provides effective postoperative pain relief after major abdominal surgery as a part of multimodal analgesia.